Amizades e sociabilidades escolares no Facebook: um estudo sobre a conversação online entre jovens moradores da zona rural de Pelotas - Lima, Francisco Silva de (Universidade do Vale do Rio dos Sinos, 2014)
This present work intends to research conversations and consequent sociability among youth who lives in Pelotas` rural areas – city located in Rio Grande do Sul southern part – throughout Facebook. Specifically, it intends to realize how social relations between students have changed from the usage of this social network site. Besides that, this study searches for elements that can help comprehending how the rural youth is affected by the globalized reality of media and technological consumption. For that, the theoretical part addresses youth culture and rural youth, putting them in a context of consumption and usage of technologies, and in a context of mediations. From a communicational perspective, this study addresses sociability inserted in a networked society and the concepts of social network, social network sites, social bonds, social capital and interaction. The methodology was built as a case study, to identify some particularities of the studied group, with no generalizing intentions. In a first moment, during the exploratory movement, some regional family farmers were interviewed by telephone, and semi-structured interviews took place in a high school class with second year students, to subsidize the research design construction. Following, the usage of questionnaires and some informal conversation added to the collected data, helping to identify some group characteristics and, besides that, to identify some changes in the colleagues` interaction from Facebook usage. As results, the technology use as tool to mediate sociability, resulting in more contact between youths and, therefore, better interpersonal relationships outside school. Besides that, Facebook usage increased sociability with family and distant people, opened space for interaction with unknown and provided more access to current information. However, it was noted that offline social practices keep strongly present among this particularly youth, because not all of them have access, or because some of them don`t master the languages and technical aspects of internet and social network sites (yet).
Keywords: Culturas juvenis; Juventude rural; Facebook; Conversação; Sociabilidade; Youth culture; Rural youth; Facebook; Conversation; Sociability; ACCNPQ::Ciências Sociais Aplicadas::Comunicação